2012
DOI: 10.1590/s1516-05722012000100018
|View full text |Cite
|
Sign up to set email alerts
|

Use of extracts of sunflower-seed oil (Helianthus annus L.) for the treatment of cutaneous injuries in equine metatarsus: a case report

Abstract: ABSTRACT:This study describes an eighteen-year-old filly after an injury in the region of the dorsal left metatarsus, admitted to veterinary assistance. In addition to the normal treatment, which was characterized by cleaning and topical application of povidone-iodine, sunflower-seed oil was applied locally in order to improve and fasten wound healing. Macroscopic and clinical improvements of the wound healing were observed. The preliminary chemical and physical analyses have shown the stearic acid as the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…A study 40 concluded that sunflower oil provides an increase in granulation tissue and complete healing of the epidermis. In other studies [41][42][43] , it was stated that sunflower oil was more effective in wound healing compared to control, and this may be due to the linoleic acid content. In our study, histological results were compatible with the literature, but when the immunohistological results were examined, it was seen that the sunflower oil group had high IL-6 and TNF-α in the wound tissue.…”
Section: The Success Ranking Of Groups At the End Of Experiments In A...mentioning
confidence: 93%
“…A study 40 concluded that sunflower oil provides an increase in granulation tissue and complete healing of the epidermis. In other studies [41][42][43] , it was stated that sunflower oil was more effective in wound healing compared to control, and this may be due to the linoleic acid content. In our study, histological results were compatible with the literature, but when the immunohistological results were examined, it was seen that the sunflower oil group had high IL-6 and TNF-α in the wound tissue.…”
Section: The Success Ranking Of Groups At the End Of Experiments In A...mentioning
confidence: 93%
“…In a study by Oliveira et al (2013), it was found that pumpkin oil increased tensile strength and increased collagen synthesis, possibly as a result of the action of fatty acids (Oliveira et al, 2013). The sunflower seed oil has positively contributed to wound healing (Coelho et al, 2012;Rodrigues et al, 2004). Oleic and linoleic acids, the main components of sunflower oil, also present in extra virgin coconut oil, demonstrated that when topically applied, promoted rapid and satisfactory healing in mice (Cardoso et al 2004).…”
Section: Vehicles For the Use Of Ozone Therapymentioning
confidence: 99%
“…Some topical preparations have already been tested in skin wounds in horses (MARTINS et al, 2003;SOUZA et al, 2006;COELHO et al, 2012.…”
Section: Introductionmentioning
confidence: 99%